The Role of Teachers in Developing Character Education in Elementary Schools: Literature Review - Syarif, Naufal Qadri (Journal for Teaching and Education for Scholars, 2025)
Teachers, as educators, are not only responsible for teaching academic material but also serve as role models, mentors, demonstrators, and motivators in shaping students' character. This study aims to analyze the role of teachers in developing character education in elementary schools. The main focus of this research is to understand how teachers act as educators, role models, and motivators in character formation. This study employs a qualitative descriptive method using a literature review technique to collect data from various sources such as journals, books, and related scientific articles. The findings reveal that teachers play a strategic role in instilling character values such as discipline, responsibility, and honesty through interactive teaching methods and a supportive learning environment. Teachers also contribute to building a school culture that supports character development by appreciating good behavior, guiding students in both academic and non-academic activities, and creating an enjoyable learning atmosphere. The conclusion of this study emphasizes that character education must become an integral part of school culture and be supported by the synergy between schools, parents, and the wider community